R Language for Environmental Design Academic Research Analysis - Jiazhen Zhang; Shixuan Dai; Chengchen Guo; Mingjie Shen; Yang Liu; Jeremy Cenci (Land)
Environmental design provides crucial solutions for achieving sustainable development goals while offering new opportunities to improve human living conditions and enhance social welfare. This study employs bibliometric analysis using the R language to examine environmental design-related journal articles collected from the WoS database between 2000 and 2024, quantitatively analyzing the overall development of the environmental design research field over the past two decades. Currently, environmental design research is experiencing rapid development. Through cluster analysis, three major research hotspots in this field have been identified: green buildings and sustainable urbanization, ecological restoration and environmental governance, and the application of intelligent technology in environmental design. Through evolution analysis, the logical development of environmental design research has been determined, with technological innovation playing a pivotal role in the field’s advancement. Following this logic, we propose three frontiers with explosive development in the environmental design field: human-centered environmental design, intelligent technology application, and regional cultural adaptability. Environmental design represents a core research direction in architecture, urban planning, and environmental science disciplines, and serves as a crucial domain for emerging technologies to empower sustainable development. The research findings clearly present the current status, evolutionary logic, and research frontiers of this field, providing valuable references for its further development.